(3GdPcGA GdGUWfGYi haYGdjJg ai egGQGJ GdHQeLIs - (3LhOg, eMeO YHOGdYRjR eMeOs ((3GdbGgQIs (3OGQ GdYde hGdEjeGf ddfTQ hGdJhRjYs, 2025)
(3jTjQ GdPcGA GdGUWfGYj aj GNJHGQ GdHQeLjGJ Edi GSJNOGe GdNhGQRejGJ hGdfeGPL GdPcjI, eKd GdJYde GdBdj heYGdLI GddZI GdWHjYjI hGdTHcGJ GdYUHjI, dJMSjf YedjI GNJHGQ GdHQeLjGJ(B. (3Jecf JbfjGJ GdPcGA GdGUWfGYj GNJHGQ GdHQeLjGJ ef Cf jUHM CcKQ GSJbdGdjI hcaGAI hObI ef NdGd eMGcGI bOQGJ GJNGP GdbQGQ GdHTQj hCJeJI GdegGe GdeJcQQIs
1 2 13 23
Keywords: (3GdPcGA GdEUWfGYis